PhD by publication or PhD by traditional model: which way to go? - Gumbo, J. R. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
South Africa is at the cross-roads with the knowledge production economy. The DST target is 6000 PhD graduates per million by 2018. The knowledge economy is important for South Africa as it is the engine for economic growth. There is a link between knowledge production and economic growth of a country by comparing the citation intensity and the economic wealth of the country. In addition to the knowledge production other factors such as political and macro-economic factors, infrastructure investments, providing clean water and sanitation, roads must be in place for sustainable economic development. This can only be sustained through the ‛production of highly trained people’ the PhD students. But the trick is which PhD model should I take? On the PhD model, the ASSAF study showed that South Africa produced most of the PhDs through the traditional model. However, for South Africa to produce more PhDs in a shorter time period there is a need to move away from the traditional model and embrace other forms of PhD production. The alternative model is the PhD by publication. This is able to produce PhD graduates in shorter pace of time with high quality impact publications.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: PhD graduate; Knowledge economy; Citation intensity; Knowledge economy; College graduates; College publications